MILLENNIAL LEADERS’ DISPLAY OF GENERATIONAL COHORT STEREOTYPES: A QUALITATIVE RESEARCH APPROACH - Louisa Grotkamp; Janina Magdalena Schaumann; Philipp Riehm (Universitas Gadjah Mada, 2020)
This paper investigates how Millennial leaders perceive themselves in their leadership role and whether generational cohort stereotypes prevail with ascending hierarchy levels. There is a lack of research, which applies generational cohort stereotypes to Millennials in a leadership context. This limits our understanding of this generational cohort and how its members can benefit organizations in their role as leaders. Millennials in leadership positions are a new and underresearched phenomenon. Therefore, an explorative, qualitative research approach was followed, including interviews at 15 organizations from different industry segments in Germany. The data was analyzed through a qualitative content analysis. The study shows that Millennial leaders displayed generational stereotypes, but also adapt their behavior to corporate structures. This is problematic since it can limit Generation Ys’ value creating potential for organizations (e.g. driving innovation). This study contributes novel insights on Millennial leadership and organizational challenges in integrating this generational cohort within corporate structures. Organizations are advised to support the development of structures and processes that allow Millennials to unfold their potential. Directions for future research are outlined to further investigate this new phenomenon.